Heparanase Is a Putative Mediator of Endothelial Glycocalyx Damage in COVID-19 – A Proof-of-Concept Study - Drost, Carolin Christina; Rovas, Alexandros; Osiaevi, Irina; Rauen, Matthias; van der Vlag, Johan; Buijsers, Baranca; Salmenov, Rustem; Lukasz, Alexander; Pavenstädt, Hermann; Linke, Wolfgang A.; Kümpers, Philipp (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is a systemic disease associated with injury (thinning) of the endothelial glycocalyx (eGC), a protective layer on the vascular endothelium. The aim of this translational study was to investigate the role of the eGC-degrading enzyme heparanase (HPSE), which is known to play a central role in the destruction of the eGC in bacterial sepsis. Excess activity of HPSE in plasma from COVID-19 patients correlated with several markers of eGC damage and perfused boundary region (PBR, an inverse estimate of glycocalyx dimensions of vessels with a diameter 4-25 µm). In a series of translational experiments, we demonstrate that the changes in eGC thickness of cultured cells exposed to COVID-19 serum correlated closely with HPSE activity in concordant plasma samples (R = 0.82, P = 0.003). Inhibition of HPSE by a nonanticoagulant heparin fragment prevented eGC injury in response to COVID-19 serum, as shown by atomic force microscopy and immunofluorescence imaging. Our results suggest that the protective effect of heparin in COVID-19 may be due to an eGC-protective off-target effect.